2020
DOI: 10.1002/cplu.202000623
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Fission in Thin Solid Films of Bis(thienyl)diketopyrrolopyrroles

Abstract: The singlet fission (SF) process discovered in bis(thienyl) diketopyrrolopyrroles (TDPPs) can boost their potential for photovoltaics (PV). The crystal structures of TDPP analogs carrying n-hexyl, n-butyl, or 2-(adamant-1-yl)ethyl substituents are similar, but contain increasingly slipped stacked neighbor molecules. The observed SF rate constants, k SF , (7 � 4), (9 � 3) and (5.6 � 1.9) ns À 1 for thin films of the three compounds, respectively, are roughly equal, but the triplet quantum yields vary strongly: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 57 publications
(144 reference statements)
1
37
0
Order By: Relevance
“…Despite the suitability of DPP dyes for SF and repeated study with TA spectroscopy 32 , 33 , 1 (TT) emission has never been reported in this family of materials. This first and direct observation of 1 (TT) emission in a DPP thin film allows us to conclude that the triplet-like PIA observed in the TA data stems from SF, not from SO-ISC.…”
Section: Resultsmentioning
confidence: 95%
“…Despite the suitability of DPP dyes for SF and repeated study with TA spectroscopy 32 , 33 , 1 (TT) emission has never been reported in this family of materials. This first and direct observation of 1 (TT) emission in a DPP thin film allows us to conclude that the triplet-like PIA observed in the TA data stems from SF, not from SO-ISC.…”
Section: Resultsmentioning
confidence: 95%
“…As a result, the S 1 lifetime is practically unaffected by the the rates of all the processes deactivating S 1 . 63 concentration, while the 1 (TT) decay is slowed down in the most dilute solutions. These results may be a further indication of an ultrafast INTRAmolecular double triplet formation followed by an INTERmolecular independent triplet separation.…”
Section: Resultsmentioning
confidence: 95%
“… b k SF = Φ SF × k S /2 where that is the sum of the rates of all the processes deactivating S 1 . 63 …”
Section: Resultsmentioning
confidence: 99%
“…In an important series of studies for understanding the effect of coupling on SF, Wasielewski et al and Michl et al , investigated how substituents on the nitrogens of diketopyrrolopyrroles (DPPs) influence SF yield. DPPs are an attractive class of chromophores for the active layers of photovoltaics because they are stable in ambient conditions, have relatively high extinction coefficients, and have highly tunable structures that permit the control of solubility, molecular packing in films, and electronic energy levels, and, importantly, they undergo SF because triplet energies are roughly half their singlet-state value. , One of the derivatives used in both studies, di- N- methylated DPP (MeDPP), exhibited nearly 200% (T 1 T 1 ) yield but only after vapor solvent annealing (VSA).…”
Section: Introductionmentioning
confidence: 99%